2015
DOI: 10.1007/s10857-015-9300-4
|View full text |Cite
|
Sign up to set email alerts
|

Challenging teacher beliefs about student engagement in mathematics

Abstract: This study explored the beliefs about student engagement in mathematics of three Year 5 and 6 teachers, focusing on the shifts that occurred during a 10-week intervention. Data obtained from teacher surveys, interviews, video-recorded workshop observations and artefacts from teachers' classrooms reveal variations in their reactions to the professional learning experiences. Teacher responses were mediated by personal and contextual elements including teacher efficacy beliefs, teacher confidence in mathematics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 46 publications
(59 reference statements)
0
28
0
4
Order By: Relevance
“…The current study is situated within a large mixed-methods project (see description by Bobis, Way, Anderson, and Martin 2016) designed to research the decline in mathematics engagement and achievement during the middle years of schooling. The larger project used cross-sectional and longitudinal research designs with quantitative and qualitative methods in order to discover broad pedagogical characteristics of mathematics teachers and inform an intervention program.…”
Section: The Current Studymentioning
confidence: 99%
“…The current study is situated within a large mixed-methods project (see description by Bobis, Way, Anderson, and Martin 2016) designed to research the decline in mathematics engagement and achievement during the middle years of schooling. The larger project used cross-sectional and longitudinal research designs with quantitative and qualitative methods in order to discover broad pedagogical characteristics of mathematics teachers and inform an intervention program.…”
Section: The Current Studymentioning
confidence: 99%
“…Aktivitas seperti ini harus tetap dilakukan di dalam kelas untuk mempertahankan motivasi dan keterlibatan siswa dalam bermatematika. Bobis et al (2016) menjelaskan bahwa pertanyaan atau tugas terbuka adalah salah satu strategi yang dapat meningkatkan motivasi, mengaktifkan siswa melalui keterlibatan matematika dan mengeksplorasi situasi dalam masalah matematika. Dengan kata lain, guru perlu menggunakan pendekatan ini di kelas dalam rangka membina siswa untuk belajar matematika dengan cara yang bermakna (Intaros et al, 2014).…”
Section: Hasil Dan Pembahasanunclassified
“…As Brady highlights, this result seems contrary to some other studies that found a correlation between discipline-based and educational mathematical beliefs, so this warrants further investigation. Bobis, Way, Anderson, and Martin (2015) also examined the beliefs of primary school teachers, and they found that the views were mediated by a range of personal and contextual factors, and their developing beliefs were influential in their professional development in mathematics education.…”
Section: Beliefsmentioning
confidence: 99%